Performance of Islamic Banks: Assessment Using Sharia Maqashid Index (SMI), Syariah Conformity and Profitability (SCnP) in Indonesia for Period 2018-2023 - Shilamaya, Putri; Hanif, H.; Etika, Citra (Golden Ratio of Finance Management, 2025)
This research evaluates the performance of Islamic banks by comparing two assessment methods, the Sharia Maqashid Index (SMI) and Sharia Conformity and Profitability (SCnP), to determine the most effective approach to balancing Sharia principles and profitability. The SMI measures performance based on three mashed Sharia objectives: education, justice, and prosperity, while the SCnP assesses both Sharia compliance and financial sustainability. The findings indicate that SCnP provides a more comprehensive evaluation, as it emphasizes adherence to Islamic principles and considers long-term financial viability. Among the banks analyzed, Bank Central Asia Syariah (BCAS) demonstrates the best balance between these aspects. In contrast, Bank Muamalat Indonesia (BMI) and Bank Victoria Syariah (BVS) prioritize Sharia compliance while facing profitability challenges. This study confirms that the SCnP method offers a more holistic assessment of Islamic banks' performance. It is a valuable reference for regulators and industry players in developing evaluation frameworks that align with modern economic dynamics without compromising Sharia principles.